Pengaruh Marketing Mix Terhadap Pelanggan Centra Fitness Bandar Lampung - Agung, Martin Aditya; Pramono, Arief; Yahya; Putra, Nanda Pramana; Syarif, Arman; Pradana, M. Rafieq Adi (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2023)
Awareness of the importance of health makes most people change their lifestyles into healthier lifestyles. One of them is making fitness as a means to achieve these healthy goals. Limited time and level of practicality, is one of the reasons why people prefer fitness to other physical sports. The spread of the number of fitness centers and fitness centers has made the level of competition even tighter, so consumers have a high bargaining position on product or service quality, product prices, strategic locations, and promotions carried out. The purpose of this study was to determine the effect of marketing mix (product, price, location and promotion ) on customer of centra fitness Bandar Lampung. The population in this study were all consumers of Centra Fitness Bandar Lampung. Data Analysis method used in this study is the validity and reliability test, where for data analysis itself uses quantitative analysis methods The study was conducted using the statement method of 30 respondent in Bandar Lampung Centra Fitness where 83,3% were male and the remaining 16,7% were female. From testing using the SPSS 22 program, it was found that there was a marketing mix effect of 41,8% on customer loyalty of Centra Fitness Bandar Lampung.